PERENCANAAN CHECK DAM SUNGAI DAWE KUDUS - Adibatul Mustaanah; Nur Pinandoyo; Sugiyanto Sugiyanto; Sri Eko Wahyuni (Jurnal Karya Teknik Sipil, 2013)
Juana river’s located in two administrative regions Kudus and Pati had superficial. This is because the slope of the river is quite gentle and the level of environmental degradation in the watershed (DAS) Juana river’s have increased. Based on these conditions, it is necessary to plan the construction of sediment control (check dams) to reduce sedimentation along the river and optimize the function of the Juana river’s. Planning is performed on Dawe river’s ,the branch of Juana river’s. From the calculation results obtained 7 m high main dam, main dam foundation depth of 2,8 m, width of crest main dam 32 m, the water level above the crest 1,60 m, high freeboard 0,6 m, thick of main dam crest wing 2 mand capacity of sediments for 20.851,063  m³. The total cost needed to build the check dam Dawe river’s is Rp. 6.511.846.000,00 already includes VAT and 23 weeks old craftsmanship.